Immediate Effects of Core Stabilization Exercise on β-Endorphin and Cortisol Levels Among Patients With Chronic Nonspecific Low Back Pain: A Randomized Crossover Design - Aatit Paungmali (2018)
© 2018 Objective: The main objective of the study was to measure the levels of plasma β-endorphin (PB) and plasma cortisol (PC) under lumbar core stabilization exercise (LCSE), placebo and control conditions in patients with chronic nonspecific low back pain. Methods: Twenty-four participants with chronic nonspecific low back pain participated in a randomized, placebo-controlled, crossover design study. There were 3 experimental exercise conditions: control condition (positioning in crook lying and rest), placebo condition (passive cycling in crook lying using automatic cycler), and LCSE on a Pilates device tested with a 48-hour interval between sessions by concealed randomization. A blood sample was collected before and after the exercise conditions. Plasma β-endorphin and PC were measured through enzyme-linked immunosorbent assay and electrochemiluminescence in a Cobas E411 auto analyzer. Results: A significant difference in PB level was identified before and after the LCSE condition (P <.05), whereas no significant differences were noted in control and placebo exercise conditions. Also, the trend of elevation of PB under the LCSE was significantly different compared with the placebo and control conditions (P <.01). In contrast, the PC level remained unchanged in all 3 conditions. Conclusion: The findings of this study indicate that LCSE could possibly influence PB but not PC level among patients with chronic nonspecific low back pain. The mechanism of action of the pain-relieving effect of LCSE might be related to an endogenous opioid mechanism as part of its effects and might not be involved with a stress-induced analgesia mechanism.